PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. TASPEN (PERSERO) KANTOR CABANG UTAMA SEMARANG) - Vivi Amanah Harahap; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2016)
The research was conducted due to the fluctuating performance data in PT. TASPEN (Persero) KCU Semarang in the last three years. The occurrence of the up and down performance data the company identified that motivation and work environments that exist in the company during this less noticed by the company. The purpose of this research were to determine the influence of motivation adn work environment agains employee performance and job satisfaction. The Sampling techniques used sampling jenuh means the entirety of the employees be made respondents. The respondents in this research totalled 53 respondents. This research was also using Path analysis techniques supported by SPSS software version 20.3. The validity test, reliability test, coefficient of correlation test, linear and multiple regression, coefficient of determination test, and significance tests (t and F test) with Sobel method beforehand. The results has showed that the independent variable in this study had a variable affect performance motivation through job satisfaction has no relationship mediation, and work environment that affect performance through job satisfaction had partial mediation.